Viabilidade econômica da implantação de compensadores série dinâmicos em redes de distribuição de energia elétrica - Pinto, Leandro Arthur [UNESP] (2015)
The electrical distribution system has presented constant changes to adapt to the growth in power demand with reducing financial and energetic resources availability. Utilities are looking for improvement in operating conditions using new technologies to attend to high power quality by the most demanding consumer. The use of equipment to improve the flexibility of distribution systems is an alternative which postpone large investments in system expansion. The thyristor-controlled series compensator is an attractive option for networks up to 36 kV. In this work, flexible solutions are discussed to postpone investments. Economical viability of a series controlled compensator in a distribution system is presented. The results take in account the initial cost, time of implementation, return on invested capital, among others